Optimizing Utilization by Using Promodel and Fmea Queue Methods at Toll Gates - Eka Febriana, Monalisa; Endih Nurhidayat , Asep (Jurnal Indonesia Sosial Sains, 2023)
PT Citra Marga Nusaphala Persada Tbk is a toll road company headquartered in Jakarta, Indonesia. Until the end of 2020, this company holds concessions for five toll roads in Java Island. Looking at the queue report, it can be seen that there are still a large number of vehicle queues on the highest toll roads, namely 65 vehicles at 19.00-20.05 hours. Long queue lengths can affect customer dissatisfaction with the service system on the toll road so that it can be detrimental to the company, moreover the lack of maximum automatic machine work is the main factor in long queues. Of all the problems that occur can be solved using the queuing method and FMEA. The goal is to find out how to deal with queues on toll roads and find out how to deal with automatic machines working optimally. Based on the results that have been obtained, the company only opened 2 automatic substation machines. There are many obstacles that occur, including there are still queues due to the less than optimal machine work. So that this research was carried out to fix the problem that occurred by adding 1 automatic substation machine. The difference in the utilization rate is very large, namely 10.96% to 31.51%, with the result that the number of vehicles waiting is 0, meaning there are no vehicles queuing. The high RPN results from the results of the FMEA method make it the basis for the need for preventive maintenance measures to avoid total engine shutdown which results in long queues at toll exits. This action consists of providing maintenance workers who guard the substation to guard against machine problems by working 3 shifts and periodic checks starting from the system to its components.